Regulation, Innovation, and Systems Integration: Evidence from the EU - Carlo Cambini; Raffaele Congiu; Golnoush Soroush (Energies, 2020)
Energy systems integration (ESI) provides a holistic view of the electricity, gas, and heat sectors, which allows the identification and delivery of system solutions that lead to an overall cost efficiency while granting the reliability of the energy system. In this paper, we search for evidence of investments in ESI in the EU to assess whether policymakers are incentivizing its adoption adequately. To do so, we examine how innovation is being fostered in the energy sector in six EU countries by looking at the incentives provided by each country’s regulatory system. We look for evidence on investments in ESI-enabling technologies or ESI projects. We find a variety of approaches towards incentivizing innovation, which range from regulation-driven to government-driven ones. Preferences for different technologies emerge on a per-country basis. Nevertheless, what appears as most striking is the low level of investments throughout the six countries, both for ESI-enabling technologies and ESI projects. Although ESI’s role in the EU’s green transition has been recognized, there is still a need for technological and policy solutions to foster its adoption.